2014
DOI: 10.1007/s00401-014-1381-0
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil recruitment to the brain in mouse and human ischemic stroke

Abstract: Neutrophils are rapidly recruited in response to local tissue infection or inflammation. Stroke triggers a strong inflammatory reaction but the relevance of neutrophils in the ischemic brain is not fully understood, particularly in the absence of reperfusion. We investigated brain neutrophil recruitment in two murine models of permanent ischemia induced by either cauterization of the distal portion of the middle cerebral artery (c-MCAo) or intraluminal MCA occlusion (il-MCAo), and three fatal cases of human is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
354
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 350 publications
(375 citation statements)
references
References 52 publications
18
354
2
1
Order By: Relevance
“…Discussing this study in an editorial (30), it was suggested that granulocyte extravasation in ischemic infarct lesions may depend on the severity of the ischemic tissue injury and the presence of a hemorrhagic component in the lesions. Perez de Puig et al supported this view by detecting extravasation of PMNs in fatal cases of human stroke lesions and in animal models and hypothesized PMNs access to the parenchyma from the perivascular space and the leptomeninges after prolonged occlusion through activation leading to NETosis (40). However, in our study, complete tissue necrosis has been seen in the center of all cases with acute lesions, and diffuse granulocyte infiltration of the lesions was also largely absent in most cases with a hemorrhagic component.…”
Section: Relation Of the Inflammatory Reaction To Blood Vesselssupporting
confidence: 70%
“…Discussing this study in an editorial (30), it was suggested that granulocyte extravasation in ischemic infarct lesions may depend on the severity of the ischemic tissue injury and the presence of a hemorrhagic component in the lesions. Perez de Puig et al supported this view by detecting extravasation of PMNs in fatal cases of human stroke lesions and in animal models and hypothesized PMNs access to the parenchyma from the perivascular space and the leptomeninges after prolonged occlusion through activation leading to NETosis (40). However, in our study, complete tissue necrosis has been seen in the center of all cases with acute lesions, and diffuse granulocyte infiltration of the lesions was also largely absent in most cases with a hemorrhagic component.…”
Section: Relation Of the Inflammatory Reaction To Blood Vesselssupporting
confidence: 70%
“…66,67 These neutrophil extracellular DNA traps have been shown to bind platelets, red blood cells, and provide a matrix for the activation of the coagulation contact pathway. 61,66 Signs of neutrophil extracellular DNA trap formation were recently described in experimental stroke, 68 and the DNA-degrading enzyme DNase-1 was shown to reduce ischemic brain injury. 69 Additional studies are needed to assess the potentially adverse prothrombotic effects of neutrophils in cerebral ischemia and reperfusion injury to better understand their thromboinflammatory role in stroke.…”
Section: Inflammatory Cellsmentioning
confidence: 97%
“…Stroke remains the leading cause of disability worldwide with limited treatment options (Moskowitz et al, 2010). Whereas reestablishing cerebral perfusion with tissue plasminogen activator and/or clot-retrieval devices may improve the outcome of some patients (Campbell et al, 2015a), these interventions have a short therapeutic window or are not widely available, and, as such, can be used only in a minority of stroke patients.…”
Section: Introductionmentioning
confidence: 99%